Plant species identity and richness influence microbial respiration of soil microorganisms on various functional groups in northeastern Patagonia, Argentina - Cardillo, Daniela Solange (2018)
Studies on basal soil respiration (i.e., under undisturbed conditions) are very important because they can be used as indirect indicators of the biological activity in those soils; this ecological process is recognized as the major source of carbon flux from the soil surface, and one of the crucial components of the carbon cycle in terrestrial ecosystems. The objectives of this study were to determine the microbial respiration of soil microorganisms at various levels of plant species richness and developmental morphology stages in various perennial grass (Nassella longiglumis, N. tenuis, Amelichloa ambigua), and herbaceous (Atriplex semibaccata) and woody (Larrea divaricata, Schinus fasciculatus) dicots grown in experimental plots during 2013 and 2014. There were 54 experimental plots. On each of 6 blocks, there was a plot (1.25x1.25m) for each of the 6 species (monocultures) and one plot each having combinations of 2, 4 or 6 species. Six hundred and twenty nine plants were reserved to replace dead plants in the plots [629+1944 plants from the plots (54 plots x 36 plants per plot)=2573 plants in total]. An auger (3 cm diameter, 20 cm length), was used to obtain six replicate root + soil samples at each of four sampling times during those years. Basal soil respiration was similar (p>0.05) or greater (p<0.05), but ever lower, as plant species richness increased. Our results demonstrated that the plant species differences in microbial respiration in the experimental plots were species richness-, developmental morphology stage-, and sampling-time dependents.